Plants for nitrogen management in riparian zones: A proposed trait‐based framework to select effective species. (25th July 2019) - Franklin, Hannah M.; Robinson, Brett H.; Dickinson, Nicholas M.
Summary: Restoring plants to the riparian zone is regarded as management best practice in river restoration and has the potential to reduce the impact of nitrogen (N) pollution on aquatic organisms and improve water quality for human use. Plant characteristics and the interplay of hydrology and biogeochemistry control N retention in the riparian zone. The balance between processes such as denitrification and plant assimilation determines riparian N retention. Plant traits are likely to mediate these N removal processes through variations in root form, growth character, foliage production (quantity, quality and rate of return to the soil) and by altering conditions in the rhizosphere soil. Vegetation can slow N transfer via direct plant uptake of N (during periods of rapid vegetation growth) and changes induced to soil hydrology, nutrient cycling and microbial activity, principally denitrification. Few studies have focused on species‐dependent effects on N movement through soil and across boundaries. We propose a new framework, based on a literature review of plant traits with respect to N cycling, which can be used to select plant species with traits likely to maximise N removal during transport through the riparian zone. In the proposed framework, inter‐specific differences in traits known to influence N mobility: root form, growth rate, foliar characteristics and rhizosphere processes, are used to describe species' potential impact on N removal. Plant trait data may be drawn from studies outside the riparian zone; for example forest ecology, horticulture or forestry research, and candidate species are scored to predict N removal efficiency. We apply the framework to New Zealand's native riparian plant assemblages to demonstrate the trait‐based approach. This framework can guide restoration management decisions and investment in riparian revegetation in a manner that is not restricted to geographically specific or well‐studied species.